Modelling and physical analysis of the high-temperature rheological behavior of a metallic glass. (November 2021) - Cheng, Y.T.; Hao, Q.; Pelletier, J.M.; Pineda, E.; Qiao, J.C.
Highlights: High-temperature rheological behavior of a metallic glass was investigated. Plastic deformation behavior and apparent viscosity strongly depend on temperature and strain rate. Physical origin of the stress overshoot is analyzed based on the physical expressions of the parameters in the free volume model. Strength of the stress overshoot is determined by the time of change from non-equilibrium to equilibrium defect concentrations. Abstract: The high-temperature rheological behavior, around the glass transition temperature, of a Zr48 Cu34 Ag8 Al8 Pd2 metallic glass was investigated by strain rate jump experiments. The results show that the plastic deformation behavior and apparent viscosity strongly depend on temperature and strain rate. The high temperature rheology can be interpreted within the framework of the free volume model. The relative defect concentration deduced from the free volume model depends on temperature and strain rate and it explains the evolution of apparent viscosity within testing conditions, which is inversely correlated with the defect concentration. The stress overshoot is found to be a characteristic feature of the high-temperature rheological behavior. The origin of the stress overshoot is analyzed based on the physical meaning of the parameters in the free volume model. The results demonstrate that the strength of the stress overshoot is determined by the time of change from non-equilibrium to equilibrium defect concentrations. This study highlights the link between the stress overshoot phenomenon and the initial structural state, examining the influence of physical aging and stress relaxation on the high-temperature deformation process of metallic glasses.